A qualitative study of GP, NP and patient views about the use of rapid streptococcal antigen detection tests (RADTs) in primary care: 'swamped with sore throats?'. Issue 4 (3rd April 2013) - Leydon, Gerry M; McDermott, Lisa; Moore, Mike; Williamson, Ian; Hobbs, F D Richard; Lambton, Tessa; Cooper, Rebecca; Henderson, Hugo; Little, Paul
Abstract : Objective: To explore patient and healthcare professionals' (HCP) views of clinical scores and rapid streptococcal antigen detection tests (RADTs) for acute sore throat. Design: Qualitative semistructured interview study. Setting: UK primary care. Participants: General practitioners (GPs), nurse practitioners (NPs) and patients from general practices across Hampshire, Oxfordshire and the West Midlands who were participating in the Primary Care Streptococcal Management (PRISM) study. Method: Semistructured, face-to-face and phone interviews were conducted with GPs, NPs and patients from general practices across Hampshire, Oxfordshire and the West Midlands. Results: 51 participants took part in the study. Of these, 42 were HCPs (29 GPs and 13 NPs) and 9 were patients. HCPs could see a positive role for RADTs in terms of reassurance, as an educational tool for patients, and for aiding inexperienced practitioners, but also had major concerns about RADT use in clinical practice. Particular concerns included the validity of the tests (the role of other bacteria, and carrier states), the tension and possible disconnect with clinical assessment and intuition, the issues of time and resource use and the potential for medicalisation of self-limiting illness. In contrast, however, experience of using RADTs over time seemed to make some participants more positive about using the tests. Moreover, patients were much more positive about the place of RADTs in providing reassurance and in limiting their antibiotic use. Conclusions: It is unlikely that RADTs will have a (comfortable) place in clinical practice in the near future until health professionals' concerns are met, and they have direct experience of using them. The routine use of clinical scoring systems for acute upper respiratory illness also face important barriers related to clinicians' perceptions of their utility in the face of clinician experience and intuition.